2010
DOI: 10.1179/016164109x12608733393836
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of Rosai–Dorfman disease involving the central nervous system

Abstract: Rosai-Dorfman disease involving the central nervous system appears to be more common than previously thought and may well assume a more prominent place in the differential diagnoses of dural-based lesions. Expert awareness of the characteristic histopathology and immunohistochemistry of the disease is required for accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 39 publications
1
83
1
7
Order By: Relevance
“…In a few cases treatment with steroids or surgical resection is necessary [3]. Extranodal involvement has been reported in up to 43%, affecting various organs, including the upper respiratory system, skin, orbita, bones, genitourinary system, endocrine glands, central nervous system, oral cavity, and soft tissues [1,4]. In a study of 423 patients Foucar et al found that 8% of the patients have bone involvement [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a few cases treatment with steroids or surgical resection is necessary [3]. Extranodal involvement has been reported in up to 43%, affecting various organs, including the upper respiratory system, skin, orbita, bones, genitourinary system, endocrine glands, central nervous system, oral cavity, and soft tissues [1,4]. In a study of 423 patients Foucar et al found that 8% of the patients have bone involvement [1].…”
Section: Introductionmentioning
confidence: 99%
“…Extranodal involvement occurs in 43% of cases 4 , and by December 2008 111 cases of Rosai-Dorfman disease involving the central nervous system had been reported in the literature. 5 The main histopathological differentiation between plasma cell granuloma and Rosai-Dorfman disease is a careful appraisal of the morphological features together with the absence of emperipolesis in the S100 positive histiocytes. 5 It has also been demonstrated that some cases of idiopathic hypertrophic pachymeningitis show the histopathological features of meningeal plasma cell granulomas and occasionally show pseudo-tumoral thickening of the dura.…”
mentioning
confidence: 99%
“…5 The main histopathological differentiation between plasma cell granuloma and Rosai-Dorfman disease is a careful appraisal of the morphological features together with the absence of emperipolesis in the S100 positive histiocytes. 5 It has also been demonstrated that some cases of idiopathic hypertrophic pachymeningitis show the histopathological features of meningeal plasma cell granulomas and occasionally show pseudo-tumoral thickening of the dura. 3 As all three conditions are rare, their radiological features can easily be confused with meningeal carcinomatosis and histological features can be easily confused with other diseases like plasmacytoma or lymphoplasmacyte-rich meningioma.…”
mentioning
confidence: 99%
“…CNS RDD may mimic meningioma on neuroimaging. 8,9 The lesion in our patient was initially diagnosed as meningioma, but due to its rapid expansion, RDD was suspected. Bone destruction and hyperostosis may be associated with meningioma but has not been reported in RDD.…”
Section: Sectionmentioning
confidence: 99%
“…A definite diagnosis of RDD is made histopathologically with characteristic features of S100 protein-positive histiocytes and emperipolesis described. 8 In the absence of systematic studies, clinical care can only be based on anecdotal reports and case series. The recurrence rate of surgically resected RDD was reported at 14% in a case series of 29 patients.…”
Section: Sectionmentioning
confidence: 99%